PENGARUH FINANCIAL DISTRESS, BOOK TAX GAP DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022) - Tara, Elda; Effriyanti (Jurnal Nusa Akuntansi, 2024)
This research aims to analyze the influence of financial distress, book tax gap, and capital intensity on tax avoidance. This type of research is quantitative with an associative approach. The research population is primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2018 - 2022. The sampling technique used was purposive sampling technique. Hypothesis testing uses panel data regression with the help of the e-views version 12 statistical tool. The research results show that financial ditress and book tax gap have no influence on tax avoidance. meanwhile, capital intensity has an influence on Tax Avoidance. Simultaneously financial ditress, book tax gap and capital intensity have an influence on tax avoidance.